LANGUAGE AS A FACTOR AND MEANS OF NATIONAL IDENTITY OF THE POPULATION OF BOSNIA AND HERZEGOVINA: HISTORY AND MODERN TIME - O. Novikova (Гуманитарные и юридические исследования)
The article deals with the specifics of the development of ethno-linguistic relations in Bosnia and Herzegovina in different historical periods. At present, in the period of aspiration of the world community for unification of economic and cultural development of countries and regions and activation of processes of the opposite character (aggravation of sense of national consciousness and national identity), the question of factors and means of national identity is actual. The article proves the influence of internal and external factors on the formation of national identity of the population of Bosnia and Herzegovina. Internal factors of genetic, religious, cultural and linguistic self-determination include the complex ethno-religious picture of Bosnia and Herzegovina, differences in the socio-economic and cultural development of individual territories and ethnic groups. External factors include the influence of foreign cultural traditions of different States (the Ottoman Empire, Austria-Hungary, etc.), which Bosnia and Herzegovina experienced in different periods of its history. The author concludes that the population of Bosnia and Herzegovina perceives language as one of the main markers of identity. The aspiration of various ethnic groups to the national identity through the substantiation of the identity of language is a manifestation of the so-called linguoregionalism. The language in this region is not a means of consolidation, but a form of ethnic opposition.